The institutional approach on coopetition - Monticelli, Jefferson Marlon (Universidade do Vale do Rio dos Sinos, 2017)
Coopetition is a multifaceted, multilevel, and paradoxical strategy of relationship between firms (LUO, 2004; CHEN, 2008; GNYAWALI; PARK, 2009). Despite the significant number of studies related to the concept, coopetition is still considered as a concept in progress. Studies have been limited in exploring a variety of firms, mainly small and medium enterprises (SMEs), although coopetition can generate relevant benefits for these firms (BOUNCKEN et al., 2015). Coopetition must be analyzed from a multi-dimensional view, considering the influence of institutional arrangements on competition, cooperation, and coopetition strategies between firms. Moreover, there is an increased competitive pressure. Firms search for coopetition to gain positioning in international markets (FESTA et al., 2017). My thesis focus on the gap that associates coopetition, formal institutions, and international performance because there are rare and inconclusive studies about these constructs. Thus, this thesis aims to highlight the relationship between formal institutions and international performance of firms from an emerging economy taking into account the role of the coopetition. Although this research focuses on different industries, they compete and cooperate in the same industry, characterizing coopetition. While connecting theoretical and empirical topics, the research question is the following: what is the relationship between formal institutions and international performance of firms from an emerging economy taking into account the role of the coopetition? This research is divided into two stages: a qualitative and a quantitative step. The qualitative stage is exploratory-descriptive. It was based on 21 interviews realized with representatives from firms and formal institutions and academic researchers to establish a case study about the context. The quantitative stage was carried out with the survey with firms from footwear, winery, and information technology industries, resulting in 166 valid responses. The analysis technique applied was regression analysis. The main contributions of this study are twofold. The first contribution is to stress the role of formal institutions in the discussion about coopetition. The second contribution is related to the research about coopetition associated with the performance in the internationalization of firms. Few studies deal with firm performance and usually focus on the innovation performance (GNYAWALI; PARK, 2009; GNYAWALI et al., 2008). As a result, a framework supporting the concept of Institutional Approach is presented. Also, results showed a direct relationship between formal institutions and international performance mediated by coopetition. Limitations of this study are based on the investigation to have occurred in a single country. At the end of this study, other avenues of the investigation appeared. First, this research focused on the inter-firm level, disregarding individual, intrafirm and network levels. Second, coopetition as context could analyze chains of agents that add value to the firms (BRANDENBURGER; NALEBUFF, 1995).
Keywords: Coopetição; Instituições formais; Desempenho internacional; PMEs em economias emergentes; Coopetition; Formal institutions; International performance; SMEs in emerging economies; ACCNPQ::Ciências Sociais Aplicadas::Administração